A systematic literature review and network meta-analysis of treatments for patients with untreated multiple myeloma not eligible for stem cell transplantation. Issue 1 (2nd January 2017) - Weisel, Katja; Doyen, Chantal; Dimopoulos, Meletios; Yee, Adrian; Lahuerta, Juan José; Martin, Amber; Travers, Karin; Druyts, Eric; Toor, Kabirraaj; Abildgaard, Niels; Lu, Jin; Van Droogenbroeck, Jan; et al.
Abstract: In newly diagnosed multiple myeloma (MM), patients ineligible for front-line autologous stem cell transplantation (ASCT), melphalan and prednisone (MP) with thalidomide (MPT) or bortezomib (VMP) are standard first-line therapeutic options. Despite new treatment regimens incorporating bortezomib or lenalidomide, MM remains incurable. The FIRST study demonstrated significant improvement in progression-free survival (PFS) and overall survival (OS) for the combination of lenalidomide and low-dose dexamethasone (Rd) until progression vs . MPT in transplant-ineligible ndMM patients. However, to date no head-to-head randomized controlled trials (RCTs) have compared Rd or MPT versus VMP. We conducted a network meta-analysis using RCTs identified through a systematic literature review to evaluate the relative efficacy of Rd versus other regimens on survival endpoints in previously untreated MM patients ineligible for ASCT. In this analysis, Rd was associated with a significant PFS and survival advantage versus other first-line treatments (VMP, MPT, MP), challenging the role of alkylators in this setting.